Os pontos sensíveis presentes no processo de apuração do ato infracional e de aplicação das medidas socieducativas: proteção ou controle dos adolescentes indesejados? - Ribeiro, Homero Bezerra (2012)
This research analyses, through the paradigm covered by the critical theories of criminology, the process of investigating of illegal act and application of educational measures for adolescents in this Statute for Children and Adolescent, approaching the major flaws present in their devices responsible for selecting, unevenly, certain unwanted persons, considered as enemies of punitive control. In this sense, through the literature method, seeks firstly to understand the main differences between the critical theory and the traditional schools of criminology (classical and positivistic), approaching how the critical theory analyses the criminalization process and the enemies choice made by the punitive social control. After, examines the historical roles for children and adolescents, especially in irregular situations, and their influence on legislations and punitive social control throughout Brazilian history, pointing, finally, that teenagers, especially pertaining to the parcels more poor, are classified as enemies. Then, it goes, through to the analysis by critical criminology, the fundamentals of illegal act and the specific characteristics of the juvenile accountability, revealing the false disputes involving the Juvenile Justice and Juvenile Criminal Justice by creating a critical model that provides all guarantees: The Infracional Justice. In addition, advocates de adoption of a alternative criminal policy capable of reducing the negative effects of juvenile accountability through the execution of children and young guarantee and the stimulus for a minimal state intervention. Finally, it analyses the critical points (or holes) presents in Statute, identifying that these gaps are accounted for selecting arbitrarily, through speeches supposedly compassionate and protectionist, certain adolescents regarded as enemies.